Analisis semiotika pidato kenegaraan terakhir Presiden Joko Widodo pada sidang tahunan MPR 2024 - Arnita, Bella; Permadi, Didi; Edy, Sarwo (Dinasti Research, 2024)
This research aims to examine the semiotic analysis of President Jokowi's final state speech at the 2024 MPR annual session through Charles Sanders Pierce's semiotic approach which involves the analysis of representamen (signs), objects (sign references), and interpretants (use of signs). This research using descriptive qualitative methods to understand the meaning and content contained in the speech. The results of the study show that